A STUDY ON EMPLOYEES’ PERCEPTION TOWARDS E-GOVERNANCE SERVICES OF KERALA GOVERNMENT - Beena, S; Amutha T (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The fundamental aim of this study is the embracement e -governance and its impact on performance of employees in public sector in Kerala. This study was carried out in chosen government offices in Southern Kerala. Online survey was applied to gather data by quantitative research methods. A total of 364 employees take part in the survey. The researcher proposed to use the non- probability sampling, choosing the convenience sampling approach due to its expedient obtainability and proximity to the researcher. The study sample institutes of senior employees and employees who carry officers’ position from all departments. Statistical analysis was achieved on the gathered data using SPSS programs. The results of the analysis supported three hypotheses. The statistical research that resulted in significant results exhibited that effort expectancy had no direct effect on the discernible intent of espousing e-governance or the influence on organizational performance. On the other hand, the putative hypotheses demonstrated that Job Fit, Compatibility, Facilitating Conditions and Performance expectancy had direct positive impact on performance of employees.